2022
DOI: 10.1128/spectrum.01413-21
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Trypanosoma cruzi in a Host Mammalian Cell Imaged in Aqueous Liquid by Atmospheric Scanning Electron Microscopy

Abstract: Using Atmospheric Scanning Electron Microscopy (ASEM), we visualized interaction between infectious stage of Trypanosoma cruzi and completely intact host mammalian cell. Plasma membrane appears translucent under ASEM, which not only enables direct observation of T. cruzi within its host cell, but also reveals internal structures of the parasite itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The compounds were also evaluated against the trypomastigote form of Trypanosoma cruzi. Trypomastigote forms are elongated, with a kinetoplast with a rounded shape located in the region posterior to the nucleus, flagellum emerging from the flagellar pocket that is located laterally, in the posterior region of the parasite (Contreras et al 2002, Takagi et al 2022. The flagellum emerges and adheres along the body of the parasite, becoming free in the anterior region.…”
Section: Evaluation Of Cytotoxic Activity Against the Forms Of Trypan...mentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were also evaluated against the trypomastigote form of Trypanosoma cruzi. Trypomastigote forms are elongated, with a kinetoplast with a rounded shape located in the region posterior to the nucleus, flagellum emerging from the flagellar pocket that is located laterally, in the posterior region of the parasite (Contreras et al 2002, Takagi et al 2022. The flagellum emerges and adheres along the body of the parasite, becoming free in the anterior region.…”
Section: Evaluation Of Cytotoxic Activity Against the Forms Of Trypan...mentioning
confidence: 99%
“…The flagellum emerges and adheres along the body of the parasite, becoming free in the anterior region. This form is highly infectious, and can be found: in the insect vector; blood and intercellular space of vertebrate hosts I have macrophages as the main host (Contreras et al 2002, Silva-Júnior et al 2022, Takagi et al 2022.…”
Section: Evaluation Of Cytotoxic Activity Against the Forms Of Trypan...mentioning
confidence: 99%
“…These amastigotes undergo extensive replication before differentiating into trypomastigotes which egress by rupturing the host cell and disperse throughout the host to infect new cells 6 . A major structural reorganization of parasite cells has been described during amastigogenesis 7 , together with changes in transcriptomic and proteomic pro les 3,[8][9][10] . However, recent work indicated that some amastigotes could enter a dormant state with reduced replicative and metabolic activity, and this process has been speci cally involved in drug escape by the parasite [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%